Ideas of identity and investment in language communities among multicultural AAVE speakers learning foreign languages - Oliha, VR (2021)
Imagined communities and investment have both been identified as dynamic forces in the process of learning a foreign language, yet few studies have explored these concepts in relation to Black foreign language learners, and even fewer still have touched on AAVE speaker status and Black multiethnic backgrounds. To address this gap in the literature, this case-study utilizes narrative interviews and short story analysis to examine the relationship between imagined communities and investment in the language learning journeys of three AAVE speaking and multiethnic, monoracial participants. Results suggest that the nuances of Black ethnic identity and the identity struggle bilingual AAE speakers in the US face have an impact on learners’ assessments of speech communities, as well as how they invest in their imagined communities. Given these findings, further research is necessary to determine how best to accommodate Black foreign language learners with differing linguistic profiles and different ethnic backgrounds in the foreign language classroom.